Consumo de serviços educacionais em cursos de graduação em gestão e negócios: Uma análise dos atributos relacionados à lealdade e retenção de alunos - Luz, André de Paula Rêgo Graciano (2018)
This study aims to understand which attributes associated with provision of educational services have greater relevance in the composition of loyalty and retention of undergraduate students in management and business courses. This is a quantitative and descriptive research that was carried out through a survey that involved the elaboration of a structured questionnaire composed of items and constructs that underwent a validation process. Firstly, study data went through an exploratory stage, then through a descriptive stage using psychometric scales analysis. Finally, the hypotheses proposed in the study were tested. The results evidenced the confirmation of hypotheses of constructs linked to relationship marketing in services which have a direct and indirect effect on loyalty and retention of clients as regards educational services. However, in the final structural model, the relationship between Affective Commitment and Loyalty is excluded, and Integration ceases to be an exogenous construct and presents itself endogenously, being influenced by the Perceived Quality and influencing the Affective Commitment, which constitutes a contribution of the study. Thus, the study demonstrates and reinforces the importance of understanding students experience in business and management courses for educational institutions.